1980
DOI: 10.1139/v80-294
|View full text |Cite
|
Sign up to set email alerts
|

Tetranortriterpenoids and related compounds. Part 25. Two 3,4-secotirucallane derivatives and 2′-hydroxyrohitukin from the bark of Guareacedrata (Meliaceae)

Abstract: 24-trien-3,21-doc acid 1, the corresponding 3-monomethyl ester 12, and 2'-hydroxyrohitukin 13, have been isolated from the bark of Glrcrrecl cedrcttrr (Meliaceae). The structuresof 1 and 12 were confirmed by correlation with methyl 3-oxotirucalla-8.24-dien-21-oate (methyl isoelemonate) 6. The 'Hand I'C nmr data are reported.On a isole, de I'ecorce de Glrrrrrcl ceclrrrtcl (Meliaceae), trois triterpenoides nouveaux, I'acide 3,4-secotirucalla-4(28).7,24-tritn-3,21-dioique 1, son ester rnethylique 12 et 2'-hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
1
6
0
Order By: Relevance
“…Ring A-seco protolimonoids structurally similar to compounds 2 and 3, are entandrolide, isolated from the seeds of E. angolense (Okorie and Taylor, 1977) and the carboxylic acids 4 and 5 from the bark extract of Guarea cedrata (Akinniyi et al, 1980). The 13 C NMR frequencies reported for them are consistent with our assignments.…”
Section: Resultssupporting
confidence: 83%
“…Ring A-seco protolimonoids structurally similar to compounds 2 and 3, are entandrolide, isolated from the seeds of E. angolense (Okorie and Taylor, 1977) and the carboxylic acids 4 and 5 from the bark extract of Guarea cedrata (Akinniyi et al, 1980). The 13 C NMR frequencies reported for them are consistent with our assignments.…”
Section: Resultssupporting
confidence: 83%
“…34 The only difference between 4 and 11 is similar to the difference between 3 and 9. 1 H-1 H COSY and HMBC spectra in 4 exhibited the presence of a 2-hydroxy-3-methylpentanoate group, which was replaced by 3-methylbutanoate moiety in 11.…”
Section: Resultsmentioning
confidence: 85%
“…Its IR spectrum exhibited typical absorptions for hydroxy (3423 cm − 1 ), ester carbonyl (1697 cm − 1 ), ether (1268, 1142, 1075 cm − 1 ), and double bond (1652 cm − 1 ) functionalities. The UV spectrum showed a peak at 220 nm due to the π-π * transition of an α,β-unsaturated carbonyl group [8,11]. The 13 C NMR spectrum of 1 provided evidence for a conjugated ester carbonyl group by signals at δ C = 167.6 (C-1') and of two olefinic carbon atoms at δ C = 137.8 (C-3') and 130.1 (C-2').…”
Section: Resultsmentioning
confidence: 99%
“…A few pharmacological studies demonstrated anti-inflammatory, antiviral, and antiprotozoal activities of some Guarea extracts [3][4][5][6]. Previous phytochemical investigations on this genus led to the isolation and identification of a wide variety of constituents including sesqui-, di-, and triterpenes, limonoids, steroids, flavonoids, and coumarins [3,[7][8][9][10]. Although a high number of chemical studies on the genus Guarea have been reported, none is known on Guarea mayombensis Pellegr., which is a big tree up to 10-15 m high, commonly distributed in tropical Africa.…”
Section: Introductionmentioning
confidence: 99%